(untitled) (Altre Modernità, 2013)
Through a language tainted by an apocalyptic vision, in 2005 the writer Alonso Cueto causes a deep impression on the public with a novel about one of the scariest times of the Andean country: Grandes miradas. This novel evokes the nonsense imposed by the duo Fujimori-Montesinos; they become kings in a coven, they are demons who prevent the end of days. The death of Guido, a judge of the good, in the manner of Jesus Christ-cedes the throne of heavenly power to Gabriela, his girlfriend, fallen angel who put on an equal footing with the beast "Montesinos" to reveal the truth that citizens from Lima have forgotten under the anmesia cultivated. This book reaches its climax with a recreation of the Revelations: the process of unmasking the Absolute Evil. Reality and mythology are mixed to light a Postmodern Apocalypse, embodied in the struggle of ordinary people against dictatorships disguised by the absolute power.